Tips for writing a case report for the novice author - Sun, Zhonghua (Wiley, 2013)
A case report is a description of important scientific observations that are missed or undetectable in clinical trials. This includes a rare or unusual clinical condition, a previously unreported or unrecognized disease, unusual side effects to therapy or response to treatment, and unique use of imaging modalities or diagnostic tests to assist diagnosis of a disease. Generally, a case report should be short and focussed, with its main components being the abstract, introduction, case description, and discussion. This article discusses the essential components of a case report, with the aim of providing guidelines and tips to novice authors to improve their writing skills.